2015
DOI: 10.1038/ncomms8671
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3ζ coordinates adipogenesis of visceral fat

Abstract: The proteins that coordinate complex adipogenic transcriptional networks are poorly understood. 14-3-3ζ is a molecular adaptor protein that regulates insulin signalling and transcription factor networks. Here we report that 14-3-3ζ-knockout mice are strikingly lean from birth with specific reductions in visceral fat depots. Conversely, transgenic 14-3-3ζ overexpression potentiates obesity, without exacerbating metabolic complications. Only the 14-3-3ζ isoform is essential for adipogenesis based on isoform-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(134 citation statements)
references
References 66 publications
5
128
1
Order By: Relevance
“…LDHA is known to be regulated by other oncogenes such as HIF-1a during cancer progression, thus cancer cells have expanded regulatory mechanism to confer metabolic advantages in the advanced stages of diseases. Previous studies showed that 14-3-3ζ is involved in multiple functions including chemoresistance, epigenetics regulation, adipogenesis and metastasis [11, 3335]. Here, we demonstrated a novel role of 14-3-3ζ in cancer cell metabolism and our findings bring new insights into the mechanistic understanding of 14-3-3ζ overexpression-mediated breast cancer initiation and progression of early-stage breast diseases.…”
Section: Discussionsupporting
confidence: 66%
“…LDHA is known to be regulated by other oncogenes such as HIF-1a during cancer progression, thus cancer cells have expanded regulatory mechanism to confer metabolic advantages in the advanced stages of diseases. Previous studies showed that 14-3-3ζ is involved in multiple functions including chemoresistance, epigenetics regulation, adipogenesis and metastasis [11, 3335]. Here, we demonstrated a novel role of 14-3-3ζ in cancer cell metabolism and our findings bring new insights into the mechanistic understanding of 14-3-3ζ overexpression-mediated breast cancer initiation and progression of early-stage breast diseases.…”
Section: Discussionsupporting
confidence: 66%
“…This is a plausible scenario because proinflammatory cytokines can also affect other biological processes that control Akt function such as protein synthesis 2 and/or Akt targeting/shuttling, 2 which is known to be important for controlling Akt destiny and function. 39 14-3-3ζ stimulates PI3K signaling 59 and also activates PDK1, thus its presence could be important but not essential 60 to induce Akt activation, those properties in 14-3-3ζ could explain in part the tumor-promoting function attributed to 14-3-3ζ upregulation. 61 Additionally, the ratio maintained between the dimeric and monomeric forms of 14-3-3ζ might have a role in controlling Akt activity; and it is possible that oscillations in the amount of p14-3-3ζS58 are necessary not only to maintain the Akt signal but also to control its cellular localization, which is important because Akt phosphorylates at least 100 non-redundant substrates in different cell compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of white adipose tissue (WAT) that defines obesity can occur through both adipocyte hypertrophy (lipid filling) and hyperplasia (adipogenesis or increased differentiation of adipocyte precursor cells into adipocytes), but the mechanisms controlling these processes have not yet been fully delineated (Berry et al 2014, Lim et al 2015. Biochemical studies have shown that insulin plays key roles in regulating white adipocyte lipid accumulation, by inhibiting lipolysis as well as promoting fatty acid uptake and triglyceride synthesis (lipogenesis) and also by stimulating the expression of genes involved in lipid uptake and storage (Kersten 2001, Czech et al 2013 (Fig.…”
Section: Direct Mechanisms By Which Insulin May Influence Obesitymentioning
confidence: 99%
“…2). Over a longer term, insulin signaling can drive adipogenesis, an orchestrated progression of events involving transient expression of the transcription factors CCAAT/enhancer-binding protein (C/EBP) β and C/EBPδ leading to induction of the master adipogenic regulators C/EBPα and peroxisome proliferator-activated receptor (PPAR) γ (Cook & Cowan 2008, Berry et al 2014, Lim et al 2015. Recently, it has also been shown that hyperinsulinemia promotes adipose tissue inflammation in mice, which contributes to disruption of metabolic processes such as de novo lipogenesis in WAT .…”
Section: Direct Mechanisms By Which Insulin May Influence Obesitymentioning
confidence: 99%
See 1 more Smart Citation